2021
DOI: 10.1021/acs.jpcc.1c06467
|View full text |Cite
|
Sign up to set email alerts
|

Imaging Valence Electron Dynamics during Surface Diffusion

Abstract: The motion of valence electrons dictates the course of several physical transformations and chemical reactions of great importance in biology and for technological applications. Direct observation of bond breaking and making is an invaluable tool for understanding the intricate mechanism of the underlying processes. To capture these instances with atomic-scale spatiotemporal resolutions, time-resolved X-ray diffraction is a promising method, which harnesses the unique properties of ultrashort X-ray pulses from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 60 publications
0
2
0
Order By: Relevance
“…The availability of ultrashort, intense x-ray pulses from various free-electron laser sources around the globe [21,22] has opened a new array of possibilities to extend x-ray diffraction from static to time domain. TRXD is an emerging method to probe ultrafast processes in nature with atomic-scale spatial and temporal resolutions and has triggered significant theoretical [23][24][25][26][27][28][29][30][31][32][33][34] and experimental [35][36][37][38][39] research on TRXD from different molecules in recent years. Additionally, we will analyse time-dependent electronic flux densities to understand the mechanistic details of the charge migration associated with the induced dynamics.…”
Section: Introductionmentioning
confidence: 99%
“…The availability of ultrashort, intense x-ray pulses from various free-electron laser sources around the globe [21,22] has opened a new array of possibilities to extend x-ray diffraction from static to time domain. TRXD is an emerging method to probe ultrafast processes in nature with atomic-scale spatial and temporal resolutions and has triggered significant theoretical [23][24][25][26][27][28][29][30][31][32][33][34] and experimental [35][36][37][38][39] research on TRXD from different molecules in recent years. Additionally, we will analyse time-dependent electronic flux densities to understand the mechanistic details of the charge migration associated with the induced dynamics.…”
Section: Introductionmentioning
confidence: 99%
“…As a variant of time-resolved surface X-ray diffraction (TRXD), time-resolved surface X-ray diffraction at grazing incidence develops significantly with the advent of XFEL. It has been experimentally demonstrated that TRXD is capable of selectively mapping the motion of valence electrons in an adsorbate–surface system . Using a smooth limited- Q Fourier filter, which can be understood as the convolution of the detected signal with a finite box function, and a Gaussian-smoothed cutoff apodization function, the valence electrons’ motion of Cu 2 /MgO­(100) are reconstructed.…”
mentioning
confidence: 99%